Understanding the students’ learning style to enhance the effectivity of learning method: a study on accounting students - Nuzul Ibnu Hajar; Jamaluddin Dahlan; Khaerunnisa Ibnu Hajar (Journal of Accounting and Investment, 2024)
Research aims: The study aims to test the students’ learning style preferences and investigate the influence of the lecturer's teaching methods in the accounting study program.Design/Methodology/Approach: This study used the Quasi-Experimental method. This experiment research was a non-equivalent control group design joined by 552 students of the undergraduate accounting program. Every respondent completed a questionnaire regarding the individual learning style (pre-test and post-test) and filled out a score on the learning style that the lecturer had presented. Afterward, an independent sample t-test was conducted to test the relationship between students’ learning styles and the lecturer’s learning methods.Research findings: This study revealed that most students in the accounting program had a passive learning style rather than an active one. Additionally, the research found that active teaching methods were more effective for students with an active learning style compared to passive teaching methods for students with a passive learning style. There was no difference in learning styles between active and passive students under the two teaching methods because the student groups were not previously separated based on learning styles.Theoretical contribution/Originality: Understanding students' learning styles is essential to enhance the accuracy of lecturers' teaching methods in the teaching and learning process, particularly in accounting. Studies on evaluating students' learning styles and examining their relationship with lecturers' teaching methods have been widely conducted in other disciplines, except in accounting within the Indonesian context. It can provide new insights into the field of accounting education and behavior.